The Cyclops for pulmonary delivery of aminoglycosides; a new member of the Twincer™ family - Hoppentocht, M.; Akkerman, O.W.; Hagedoorn, P.; Frijlink, H.W.; de Boer, A.H. (European journal of pharmaceutics and biopharmaceutics, 2015)
[Display omitted] •Aminoglycosides are hygroscopic drugs with poor dispersion and retention properties.•Tobramycin moisture sorption is much higher for the sulfate than for the free base.•Pure aminoglycoside powders can be dispersed efficiently with a proper DPI design.•A high resistance reduces oropharyngeal deposition which yields a higher lung dose.•Using the free base and avoiding excipients further reduces the tobramycin dose. Patients infected with pathogenic bacteria have to be treated with antibiotics. When the infection is in the lungs, as for instance in cystic fibrosis, bronchiectasis and tuberculosis, inhaled antibiotics have certain advantages over systemically administered antibiotics. In this study, it is shown that re-designing the Twincer™ high dose disposable inhaler into a device named Cyclops enables effective dispersion of up to 50mg of pure spray dried tobramycin. This proves that spray dried tobramycin powders in the preferred size range for inhalation can be administered without applying complex particle engineering techniques and/or using excipients. Only some coarse sweeper crystals added separately are desired to minimise the inhaler losses to less than 20% at 4kPa. The fine particle fractions <5μm of the aerosol obtained from the Cyclops closely resemble the primary particle size distribution of the spray dried tobramycin powder. Moreover, without any further optimisation the Cyclops performs good with other spray dried aminoglycosides such as kanamycin and amikacin too. Therefore, the results of this study show that with an appropriate inhaler design, adapted to the physico-chemical properties of a particular drug or drug class, excellent dispersion can be achieved for high doses of pure (spray dried) drug.